Forecasting Earthquakes in Qinghai-Tibet Plateau Using Rescaled Range Analysis. Issue 1 (May 2021) - Xu, Linfeng; Chen, Jiemin; Liu, Zhixin; Liu, Yan; Tian, Jiawei
Abstract: Fractal analysis provides a powerful method for studying complicated natural phenomena. This paper employs fractal analysis to study seismology based on the statistical fractal concept and provides a simple overview for analysing the temporal distribution and fractal characteristics of seismic activity. We delve into the self-shot fractal characteristics of seismic activity by using an analysis of the Rescaled Range scale invariance of seismic time and time interval sequences.